2013
DOI: 10.3390/cancers5030786
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of 5-Hydroxymethylcytosine in Human Cancers

Abstract: Prior to 2009, 5-methylcytosine (5-mC) was thought to be the only biologically significant cytosine modification in mammalian DNA. With the discovery of the TET enzymes, which convert 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC), however, intense interest has emerged in determining the biological function of 5-hmC. Here, we review the techniques used to study 5-hmC and evidence that alterations to 5-hmC physiology play a functional role in the molecular pathogenesis of human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 143 publications
1
28
0
Order By: Relevance
“…Moreover, recent advances suggest that distinct aberrant genetic and epigenetic events, including abnormal histone modification and DNA methylation, are all important cancer hallmarks. The discovery of the ten-eleven translocase (TET) enzyme family, which converts 5-mC to 5-hmC, has added an additional layer of complexity to the epigenetic regulation of DNA methylation (27). Multiple studies are currently focusing on investigating the effect of epigenetic changes during tumor development and progression (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent advances suggest that distinct aberrant genetic and epigenetic events, including abnormal histone modification and DNA methylation, are all important cancer hallmarks. The discovery of the ten-eleven translocase (TET) enzyme family, which converts 5-mC to 5-hmC, has added an additional layer of complexity to the epigenetic regulation of DNA methylation (27). Multiple studies are currently focusing on investigating the effect of epigenetic changes during tumor development and progression (27).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the ten-eleven translocase (TET) enzyme family, which converts 5-mC to 5-hmC, has added an additional layer of complexity to the epigenetic regulation of DNA methylation (27). Multiple studies are currently focusing on investigating the effect of epigenetic changes during tumor development and progression (27). Research on DNA methylation has been of particular interest recently, mostly targeting specific genetic loci and their promoters (8).…”
Section: Introductionmentioning
confidence: 99%
“…5hmC profiling in breast and liver cancer samples by RRHP Previous studies on the role of 5hmC in cancer have shown loss of 5hmC is commonly associated with tumor development in both hematological diseases and solid tumors [15]. However, it is not clear whether the decrease of 5hmC is a result of global 5mC reduction, which is also a hallmark of tumorgenesis, or due to a different epigenetic regulation.…”
Section: Cross-platform Validations and Correlationmentioning
confidence: 88%
“…However, emerging evidence links many diseases to both the sequence and the methylation state of the DNA (absence or presence of a methyl group to the DNA backbone)(Berger et al 2009; Bird 2002; Esteller 2007; Pastor et al 2011; Portela and Esteller 2010; Rando and Verstrepen 2007; Surani et al 2007; Thu et al 2010). Most notably, although the fundamental genetic code is not altered by the presence of the methyl group, the function can be significantly altered, disrupting normal cell behavior (Branco et al 2012; Chen and Riggs 2005; Esteller 2007; Li and O’Neill 2013; Mariani et al 2013; Riggs 2002). The regulation of cellular function can be traced to guanine-cytosine rich sequences known as CpG islands interspersed throughout the genome but more prominent in the promoter regions (Berger et al 2009; Bird 2002).…”
Section: Introductionmentioning
confidence: 99%